2002
DOI: 10.1103/physrevd.65.073024
|View full text |Cite
|
Sign up to set email alerts
|

Tests ofCPTinvariance at neutrino factories

Abstract: We investigate possible tests of CPT invariance on the level of event rates at neutrino factories. We do not assume any specific model but phenomenological differences in the neutrino-antineutrino masses and mixing angles in a Lorentz invariance preserving context, such as could be induced by physics beyond the standard model. We especially focus on the muon neutrino and antineutrino disappearance channels in order to obtain constraints on the neutrino-antineutrino mass and mixing angle differences; we found, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
(32 reference statements)
1
30
0
1
Order By: Relevance
“…Neutrinos might further have unusual properties and might, for example, violate CPT. In that case neutrinos and anti-neutrinos could have different properties and LBL experiments can give very interesting limits on this possibility [56], but we will assume in this study that CPT is preserved.…”
Section: The Oscillation Frameworkmentioning
confidence: 99%
“…Neutrinos might further have unusual properties and might, for example, violate CPT. In that case neutrinos and anti-neutrinos could have different properties and LBL experiments can give very interesting limits on this possibility [56], but we will assume in this study that CPT is preserved.…”
Section: The Oscillation Frameworkmentioning
confidence: 99%
“…The idea was first suggested by Murayama and Yanagida [14] in the form of different masses for neutrino and antineutrino, based on phenomenological considerations. This proposal was formalized as a CP T -violating quantum field theory with a mass difference between neutrino and antineutrino in [15] (see also [16] 2 CP T -violating free field model A free field model in which particle and antiparticle have different masses was proposed in [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years studies of extensions of the Standard Model have shown that it is possible to have violations of the Lorentz and CPT symmetries (see Refs. [40][41][42]) and several phenomenological studies of neutrino oscillations with different masses and mixing for neutrinos and antineutrinos appeared in the literature [43][44][45][46][47][48][49][50][51][52][53][54]. We will consider this scenario in the simplest case of effective two-neutrino mixing with…”
Section: Introductionmentioning
confidence: 99%